A cryptic new species of rupicolous Hemidactylus Goldfuss, 1820 (Squamata: Gekkonidae) allied to H. aaronbaueri Giri, 2008 from the northern Western Ghats of Maharashtra, India - Khandekar, Akshay; Thackeray, Tejas; Agarwal, Ishan (Zootaxa, 2021)
We describe a cryptic new species of large-bodied rupicolous Hemidactylus allied to H. aaronbaueri from Tamhini Ghat, in Raigad and Pune districts of Maharashtra state, India. Hemidactylus tamhiniensis sp. nov. falls within the prashadi group of Indian Hemidactylus and can be diagnosed from all other members of the group by combination of several morphological characters such as its large-body size (maximum SVL 126 mm), the number of femoral pores and poreless scales between the left and right series of femoral pores in males, and the number of transverse ventral scales across the belly at mid-body. The new species differs from H. aaronbaueri based on dorsal pholidosis at mid-body, the number of undivided lamellae beneath the first finger, the number of internasal scales, and subtle colour pattern differences, besides 10.6% uncorrected ND2 sequence divergence.